ChemInform Abstract: Convergent Three‐Component Tetrazole Synthesis. Issue 40 (16th September 2016) - Chandgude, Ajay L.; Doemling, Alexander
Abstract: Microwave assisted reaction of carboxylic acid derivatives, amines, and TmsN3 provides 1, 5‐disubstituted and various 1, 5‐fused tetrazoles.